Banach Contraction Method to Solve Partial Integral-differential Equations (College of Basic Education Research Journal, 2025)
In this paper,  Banach contraction method was used to solve linear and nonlinear partial integra differential equations of  Volterra type and compared them with exact solutions to demonstrate  accuracy of the proposed method. Results revealed that  Banach contraction method is very effective, simple and  of a high accuracy to solve higher order Integro -differential equations. Four different examples were solved and compared with  exact solutions using mean squared error and absolute error. The tables and figures show  convergence of  proposed method in  solution.
Keywords: Banach Contraction Method (BCM); Partial Integro-differential equations (PIDF)